The effect of photodynamic therapy on the wound process dynamics in patients with purulent hand diseases - J. L. Chepurnaya; G. G. Melkonyan; N. T. Gul’muradova; A. A. Sorokin (Biomedical Photonics)
Despite the progress in modern surgery, the number of patients with purulent finger and hand diseases keeps growing these days in the clinical practice of surgeons. In recent years, there has been a tendency to develop more severe forms of panaritium and phlegmon in an increasingly young contingent of patients. Increasingly, doctors refuse to use the classical method of managing a postoperative wound of the hand involving the installation of drainage tubes. This phenomenon is polygenic and calls for special attention due to the frequent deplorable consequences of a treatment failure. The high urgency of this issue in Moscow Hospital No. 4 has become a rationale to study the effect of photodynamic therapy (PDT) on the course of the wound process in patients with this pathology.The purpose of this work is to develop a technique to advance the treatment outcomes for patients with purulent finger and hand diseases in case of open postoperative wound treatment.This study includes a comparative analysis of the wound process dynamics in 49 (49.5%) patients who underwent a photodynamic therapy session in the postoperative period and in 50 (50.5%) patients who received an open wound treatment after the operation. Photodynamic therapy was performed on the second postsurgical day by a laser apparatus “Atkus-2” (wave length 661 nm) with a gel form of the chlorinseries photosensitizer photoditazin in the form of an application at the rate of 1 g ml per 3–5 cm2 of the wound surface. The power density was chosen in the range of 0.1–1 W / cm2, and the time of exposure to the wound varied from 30 to 400 seconds, depending on the area of the wound.To assess the dynamics of the wound process in the postoperative period, we took measurements of all the patients’ wound areas on the 1st and 5th days, monitored the gross impression daily. In the patients who received PDT, we observed an earlier wound cleansing and remitting of the inflammatory process, acceleration of the edge epithelization, and earlier appearance of the granulation tissue by an average of 2 days. In the group of patients who were treated with PDT in the postoperative period, on the 5th day, the wound defect decreased by an average of 1 cm2, which amounted to 22.4%, in the control group – by 18%. The analysis of cytological and morphological patterns also revealed an accelerated switch from the inflammatory stage of the wound process to the reparative one - the reparative processes in the PDT group began earlier by 2 days. The microbiological analysis of wound exudate showed a downregulation of microflora after a PDT session - only in 6 cases pathogens were identified in the repeated seeding, which amounted to 12.24% of the group compared to 38% of the control group. After a session of photodynamic therapy, patients noted a significant reduction in pain, including during dressings. The pain syndrome immediately after the session decreased by 2–3 points. By the 5th day it became moderate – 4–5 points. In the control group, this indicator on the 2nd day was 8 points, decreasing by the 5th day to 6 points. For all analyzed indicators, the groups had statistically significant differences (p <0.001). Acceleration of postoperative wounds healing enabled to shorten the inpatient stay by 6 days and bring a vast improvement to the treatment quality for this group of patients, which allows considering photodynamic therapy as a high potential method for postoperative treatment of purulent finger and hand diseases.